Research on the Influencing Factors of Movie Popularity based on Random Forest - Wei , Zhuwen; Zhang, Yifan (Transactions on Computer Science and Intelligent Systems Research, 2024)
Movie, also known as moving or moving pictures, or "reflections," is a form of visual art that communicates ideas, stories, cognitions, emotions, values, or various atmospheric simulated experiences through the use of moving images. As the mainstay of cultural industry, film has brought huge economic and social benefits, and the box office is the most important index to measure the economic benefits of film. In this study, the prediction results of the random forest analysis model are acceptable, it is well in line with the structure of the data, which is conducive to the analysis of the data, and the data is displayed with charts and graphs at the same time, so as to show the readers the indicators and data used in this topic more clearly and clearly, which increases the scientific nature of this paper. This study provides more scientific and accurate strategies for decision-makers and creators, and contributes to the high-quality dissemination of short videos.